Surgical Approach to Dentigerous Cyst with Protection of the Inferior Alveolar Nerve - Dalampiras Stylianos (Balkan Journal of Dental Medicine, 2016)
Aim: To stress the importance of surgical planning when treating large dentigerous cysts.